Effect of bariatric surgery on postoperative outcomes of total hip arthroplasty: An updated systematic review and meta-analysis - Pablo Palacios; Isabel Palacios; Ana Palacios; Alejandro Lorente; Gonzalo Mariscal; María Benlloch; José Palacios (Asian Journal of Surgery)
Bariatric surgery may cause complications following total hip arthroplasty (THA); however, the evidence remains unclear. This review aims to evaluate the effects of bariatric surgery on THA complications. A systematic search of PubMed, EMBASE, Scopus, and Cochrane databases was performed. The eligibility criteria were cohort studies comparing THA patients with and without prior bariatric surgery. The primary outcomes were complications, length of hospital stay, readmission rate, and cost. The study quality was assessed using the MINORS criteria. The meta-analysis was performed using Review Manager 5.4. Nine cohort studies (170,882 patients) met our inclusion criteria. Bariatric surgery was not associated with the risk of dislocation at 90 days (OR 1.50, 95%CI 0.83, 2.70). However, at one-year follow-up, the dislocation rate was significantly lower in the NBS group (OR 1.51, 95%CI 1.23, 1.86). Bariatric surgery reduced the risk of periprosthetic fracture risk (OR 0.56, 95%CI, 0.33 to 0.96) but had no effect on infection (RR 0.96, 95%CI 0.76 to 1.20), revision rates (OR 1.07, 95%CI 0.89 to 1.29), or survival (HR 2.41, 95%CI 0.78 to 7.42). Hospital stay was lower in the bariatric group (−0.16 days, 95%CI -0.23 to −0.09) as were 30-day readmissions (OR 0.17, 95%CI 0.07 to 0.40). The total costs showed no significant differences between the groups (MD 2323.06, 95%CI -3274.80 − 7920.93). Bariatric surgery may reduce the risk of periprosthetic fractures and decrease the length of hospital stay and 30-day readmission after THA. However, it did not significantly impact overall complications, including infection or revision rates.